The impact of health promotion on trachoma knowledge, attitudes and practice (KAP) of staff in three work settings in remote Indigenous communities in the Northern Territory. - Fiona D Lange; Kelly Jones; Rebecca Ritte; Haley E Brown; Hugh R Taylor (Public Library of Science (PLoS), 2017)
BACKGROUND:Globally, trachoma is the leading cause of infectious blindness and Australia is the only developed country with endemic trachoma. It is found in remote Indigenous communities burdened with poverty, overcrowding and poor hygiene. Lack of culturally appropriate health promotion, a small trachoma workforce and lack of awareness and support for trachoma elimination in general, were early barriers. METHODS:A cross-sectional pre-post study using a convenience sample, was conducted in clinics, schools and community work-settings from 63 of the 82 remote Aboriginal communities identified as being at risk of trachoma in the Northern Territory (NT). The study assessed the effect of a multi-component health promotion strategy aimed at increasing knowledge, attitude and practice amongst health, education and community support settings staff. Data were collected between 2010 and 2012. The health promotion initiatives were introduced in communities in staggered delivery over a one-year period; 272 participants were surveyed at baseline and 261 at follow-up. RESULTS:Trachoma related knowledge, attitudes and practice increased across all settings and for all primary outcome measures. Across all settings, there was a significant increase in the proportion of participants reporting the most important thing to do if a child has a 'dirty' face is to 'wash it every time its dirty' (61.6% cf 69.7%; X2p = 0.047), a significant reduction in the proportion of respondents answering 'no' to the question "Is it normal for kids to have dirty faces in your community' (40.5% cf 29.6%; X2p = 0.009) and a significant increase in reported capacity to teach others about trachoma prevention (70.8% cf 83.3%; X2p <0.001). CONCLUSION:Health promotion was associated with increased trachoma knowledge, attitude and practice amongst health, education and community support staff working with children and in remote NT communities. In the early stages of the trachoma health promotion program, this increased trachoma awareness and improved local workforce capacity and support for trachoma elimination in three health promotion settings in remote communities in the NT.